Renne Pennington & Henry Harpeding: The Structure ofan African Pastoral Community: Demography, History, and Ecology of the Ngamiland Herero - Kirumira, Edward K. (Tidsskriftet Antropologi, 1995)
Community: Demography, History, and Ecology of the Ngamiland Herero Anmeldes af Edward K. Kirumira.